Assessment of role of genetic polymorphisms in XRCC1, XRCC2 and XRCC3 genes in cervical cancer susceptibility from a rural population: a hospital based case-control study from Maharashtra, India - Datkhile, Kailas D.; Patil, Madhavi N.; Durgawale, Pratik P.; Joshi, Shreepad A.; Korabu, Kalpita S.; Kakade, Satish V. (International Journal of Research in Medical Sciences, 2018)
Background: Cervical cancer is a major concern of health risk, moreover the leading cause of cancer causing deaths in women of rural parts of India. This study was aimed to assess the risk of cervical cancer development in association with polymorphisms in X-Ray Cross Complementing Group (XRCC1, XRCC2 and XRCC3) genes in the rural population of south-western Maharashtra. We focused to determine the frequency of polymorphisms in DNA repair genes including XRCC1 at codon (cd) 194, cd 280, cd 399, XRCC2 at cd 188 and XRCC3 at cd 241 and their plausible role in cervical cancer risk from rural parts of India. Methods: This study included 350 proven cases with cervical cancer and 400 age and sex matched controls. We used polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) to analyze the association XRCC1, XRCC2 and XRCC3 gene polymorphisms with cervical cancer development in women of South-Western Maharashtra. Results: The result from our study showed that allele frequencies of selected genes were not statistically different between the groups for XRCC1 Trp194, XRCC2 His188 and XRCC3 Met241. XRCC1 His280 (OR= 4.36; 95% CI= (3.20-5.95); p= <0.0001) and XRCC1 Gln399 (OR= 2.99; 95% CI= (1.60-5.56); p= <0.0001) genotypes significantly increased the risk of cervical cancer. Conclusions: This study indicates that polymorphisms in cd 280 of exon 9 and cd 399 of exon 10 of XRCC1 gene could play a role in modifying genetic susceptibility of individuals towards cervical cancer among women from rural Maharashtra. This case-control study suggest that selected DNA repair genes represent genetic determinants in cervical carcinogenesis along with other risk factors in the rural Indian population.